Deliquescence‐induced wetting and RSL‐like darkening of a Mars analogue soil containing various perchlorate and chloride salts. Issue 10 (28th May 2016) - Heinz, Jacob; Schulze‐Makuch, Dirk; Kounaves, Samuel P.
Abstract: Recurring slope lineae (RSL) are flow‐like features on Mars characterized by a local darkening of the soil thought to be generated by the formation and flow of liquid brines. One possible mechanism responsible for forming these brines could be the deliquescence of salts present in the Martian soil. We show that the JSC Mars‐1a analogue soil undergoes a darkening process when salts dispersed in the soil deliquesce, but forming continuous liquid films and larger droplets takes much longer than previously assumed. Thus, RSL may not necessarily require concurrent flowing liquid water/brine or a salt‐recharge mechanism, and their association with gullies may be the result of previously flowing water and deposited salts during an earlier warmer and wetter period. In addition, our results show that electrical conductivity measurements correlate well with the deliquescence rates and provide better overall characterization than either Raman spectroscopy or estimates based on deliquescence relative humidity. Key Points: Deliquescence of salts in a Mars simulant soil sample causes a RSL‐like darkening Forming thicker liquid films or bulk water via deliquescence is a relatively slow process The deliquescence process can be investigated by electrical conductivity measurements